2008
DOI: 10.1037/0022-3514.95.5.1113
|View full text |Cite
|
Sign up to set email alerts
|

Beyond global sociosexual orientations: A more differentiated look at sociosexuality and its effects on courtship and romantic relationships.

Abstract: Sociosexuality is usually assessed as the overall orientation toward uncommitted sex, although this global approach may mask unique contributions of different components. In a large online study (N = 2,708) and a detailed behavioral assessment of 283 young adults (both singles and couples) with a 1-year follow-up, the authors established 3 theoretically meaningful components of sociosexuality: past behavioral experiences, the attitude toward uncommitted sex, and sociosexual desire (all measured by a revised ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
775
6
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 894 publications
(878 citation statements)
references
References 95 publications
40
775
6
12
Order By: Relevance
“…Future studies should thus use a measure that explicitly identifies the target of different facets of sexual behavior, dissecting the expression of desire and experience to distinguish between a woman's main sexual partner and other partners (real or imagined). We are aware that women's attitudes towards extra-pair sex is variable and that this variability may introduce further complexity in measuring effects (Levine, 2003); however, the available evidence suggests this can be informative (Garver-Apgar et al, 2006), and well-recognized measures exist to control for this variability (e.g., the revised Sociosexual Orientation Inventory) (Penke & Asendorpf, 2008).…”
Section: Future Directionsmentioning
confidence: 99%
“…Future studies should thus use a measure that explicitly identifies the target of different facets of sexual behavior, dissecting the expression of desire and experience to distinguish between a woman's main sexual partner and other partners (real or imagined). We are aware that women's attitudes towards extra-pair sex is variable and that this variability may introduce further complexity in measuring effects (Levine, 2003); however, the available evidence suggests this can be informative (Garver-Apgar et al, 2006), and well-recognized measures exist to control for this variability (e.g., the revised Sociosexual Orientation Inventory) (Penke & Asendorpf, 2008).…”
Section: Future Directionsmentioning
confidence: 99%
“…SOI is a trait which refers to individuals' overall preference for short-term or uncommitted sexual relationships 41 . One study in China has reported that SOI behavior and desire sub-scale scores were associated with online sexual activity (including SEM viewing) 42 .…”
Section: Limitations Of Prior Researchmentioning
confidence: 99%
“…SOI was assessed via the Revised Sociosexual Orientation Inventory 41 . The scale has 9 items that examine past sexual behavior experiences, attitude towards uncommitted sex, and desire 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 …”
Section: Soimentioning
confidence: 99%
“…We operationalized mating strategy with the Revised Sociosexual Orientation Inventory (SOI-R; Penke & Asendorpf, 2008). The SOI-R is a nine-item measure of an individual's cognitive, behavioral, and attitudinal disposition toward uncommitted sexual relations.…”
Section: Mating Strategymentioning
confidence: 99%
“…We also included mating strategy (Buss & Schmitt, 1993;Penke & Asendorpf, 2008) in our investigation because recent evidence demonstrates that mating strategy is a strong predictor of sexual disgust (Al-Shawaf, Lewis, & Buss, in press). If (a) disgust is related to food neophobia, and (b) mating strategy is related to disgust, then the present investigation raises the possibility of a heretofore undiscovered relationship between mating strategy and food neophobia.…”
Section: Introductionmentioning
confidence: 99%